Acute hepatitis C from heterosexual transmission. (2018) - Dias, Cátia; Pipa, Sara; Mota, Margarida
Abstract: The diagnosis of acute hepatitis C (HCV) infection is rare since the majority of cases are asymptomatic, which makes the infection usually detected in a chronic phase, most of the time using serological tests. The main route of HCV transmission is percutaneous, with sexual transmission occurring more often in men who have sex with men. The analytical alterations of acute hepatitis C are varied but usually present with ALT elevation higher than AST, very rarely with hepatic insufficiency. We report a case of a patient with a clinical and analytical picture compatible with toxic acute hepatitis, accompanied by hepatic insufficiency, with negative serology for hepatotropic viruses and with no history compatible with the use of substances with hepatic toxicity other than alcohol. During the diagnostic investigation it was concluded that the patient had acute HCV hepatitis and that the transmission route was heterosexual.